The MP marching at the head of his 300 jontlemen !!! - (:unkn) unknown (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Catholic emancipation; Great Britain -- Relations -- Ireland; Great Britain -- Politics and government -- 1800-1837